The man with the iron fists [videorecording (DVD)] - RZA (Rapper); Tarantino, Quentin; Crowe, Russell, 1964-; Liu, Lucy, 1968-; Yune, Rick, 1971-; Bautista, David, 1969-; Chung, Jamie, 1983-; Le, Cung, 1972- (Universal Studios Home Entertainment, 2013)
Bloody violence, strong sexuality, language, and brief drug use.